Correction: A bodipy based hydroxylamine sensor. Issue 77 (17th September 2018) - Sedgwick, Adam C.; Chapman, Robert S. L.; Gardiner, Jordan E.; Peacock, Lucy R.; Kim, Gyoungmi; Yoon, Juyoung; Bull, Steven D.; James, Tony D.
Abstract : Correction for 'A bodipy based hydroxylamine sensor' by Adam C. Sedgwick et al., Chem. Commun., 2017, 53, 10441–10443.